Diversity Species and Structure of Mangrove Vegetation in Conservation Forest and Angke Nature Park North Jakarta - Wulandari, Annisa; Wibisono, Muhamad Arif; Kusumahadi, Khoe Susanto; Hamdani, Moh. (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2024)
Mangrove is important life support ecosystems in coastal and marine areas that have bio-ecological and socio-economic functions. Mangroves are found in tidal areas that have the ability to grow in salty waters and have a role as a barrier to abrasion. Mangrove plants have special adaptability to the environment such as adaptation to low oxygen levels, high salinity and less stable soils. Indonesia has the largest mangrove ecosystem and the highest biodiversity in the world. This study aims to determine the index of diversity and structure of mangrove communities in Hutan Lindung Angke-Kapuk (HLAK) and Taman Wisata Angke (TWA) Angke-Kapuk which is divided into 11 points. The research was carried out on November 15 to 30, 2021 using purposive sampling techniques based on the representation element, which took 5% of the total area and the shape of a square plot with a size of 50x50 meters. The results showed that 11 family, 12 genus and 15 species of mangroves were found, the type was divided into 8 species of true mangroves and 7 species of mangroves followed. The extinction rate of mangrove species in HLAK and TWA Angke-Kapuk amounted to 1.25. The level of type similarity between research points in the HL Angke-Kapuk and TWA Angke Kapuk areas in 2020 and 2021, showed a slight change in the level of type similarity at each point. The dominant type of seedling and sapling tree level is the Avicennia marina type. Mangrove diversity index (H’) in the area of HLAK and TWA Angke Kapuk is 1.6.